2014
DOI: 10.1186/s40557-014-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Psychosocial Risk Factors and Work-Related Musculoskeletal Disorders among Public Hospital Nurses in Malaysia

Abstract: ObjectiveThis study examined the relationships between psychosocial work factors and risk of WRMSDs among public hospital nurses in the Klang Valley, Malaysia.MethodsWe conducted a cross-sectional study among 660 public hospital nurses. A self-administered questionnaire was used to collect data on the occurrence of WRMSDs according to body regions, socio-demographic profiles, occupational information and psychosocial risk factors. 468 questionnaires were returned (response rate of 71%), and 376 questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
33
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
13
33
3
5
Order By: Relevance
“…Nurses with higher BMI were considerably more likely to report discomfort in upper limbs, compared to nurses with lower BMI (OR: 1.05) [29].…”
Section: Demographic Factorsmentioning
confidence: 98%
See 3 more Smart Citations
“…Nurses with higher BMI were considerably more likely to report discomfort in upper limbs, compared to nurses with lower BMI (OR: 1.05) [29].…”
Section: Demographic Factorsmentioning
confidence: 98%
“…The relationship work-related psychosocial factors (PSFs) and musculoskeletal disorders have been greatly documented in many studies [25,28,29]. Studies demonstrated that relations of PSFs and physical exhaustion have likely increased the risk of MSDs in nurses.…”
Section: Psychological Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to global statistics it has been estimated that two million people die annually due to work-related injuries or illnesses, while there are 160 million new cases of work-related illnesses each year (3). The costs of occupational MSDs is important not only for employees, but also the employers and societies (4). It has been estimated that approximately 2% of Europe's gross domestic income is lost with the direct cost of MSDs without considering productivity losses and social costs (1).…”
Section: Introductionmentioning
confidence: 99%